1963
DOI: 10.1177/00220345630420010801
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Effect on Caries of Short-Term Feeding of Rice Hulls to Cotton Rats

Abstract: In a recent review of caries-inhibiting agents, Shawl has described and evaluated the procedures developed for experimental caries research. In general, it is useful to evaluate the anticariogenicity of a substance by incorporating it into a cariogenic diet that is fed to weanling caries-susceptible rodents. After a sufficient time for caries development in the control group, the caries inhibition by the test substance is measured.A compilation by Hein2 of a large number of assays for anticariogenic agents has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1964
1964
1995
1995

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Subsequently, this anti-caries activity was associated with the hull fractions.2 Since that time, numerous investigators have reported cariostatic capabilities of outer seed coverings of various cereal grains at levels in the diet as low as 5%. [3][4][5][6][7] Although the majority of studies have involved the use of oat hulls, the hulls of rice, peanuts, barley, and cottonseed have also exhibited anti-caries activity. In most instances, oat hulls have been shown effective against occlusal caries.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, this anti-caries activity was associated with the hull fractions.2 Since that time, numerous investigators have reported cariostatic capabilities of outer seed coverings of various cereal grains at levels in the diet as low as 5%. [3][4][5][6][7] Although the majority of studies have involved the use of oat hulls, the hulls of rice, peanuts, barley, and cottonseed have also exhibited anti-caries activity. In most instances, oat hulls have been shown effective against occlusal caries.…”
Section: Introductionmentioning
confidence: 99%